A foam cleaning agent for low corrosion rust removal and preparation method thereof

By using foam cleaning agents with components such as corrosion inhibitors, hydrophobic nano-hydroxymagnesium silicate and aluminum sulfate, hydrogen embrittlement and overcorrosion caused by existing chemical rust removers are solved, and low corrosion rust removal and repair effects are achieved. Improves the quality and service life of metal surfaces.

CN115821271BActive Publication Date: 2025-02-11TONGYOU INTELLIGENT EQUIP (JIANGSU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211576381.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2025-02-11
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

Existing chemical rust removers are prone to hydrogen embrittlement and overcorrosion when treating metals, affecting the metal strength and surface quality, and leaving dent defects to accelerate secondary corrosion.

Method used

The foam cleaning agent consisting of corrosion inhibitor, hydrophobic nano-hydroxymagnesium silicate and aluminum sulfate, and component B composed of hydrochloric acid, surfactant, and deionized water is used to achieve anti-rust and repair effects through mixing.

Benefits of technology

This cleaning agent can effectively prevent metal rust, repair dent defects, avoid secondary corrosion, and improve the quality and service life of the metal surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003989808190000071
    Figure BDA0003989808190000071
Patent Text Reader

Abstract

The invention discloses a low-corrosion rust removal foam cleaning agent and a preparation method thereof, and relates to the technical field of detergents. The present invention utilizes myristic acid, tris (2-aminoethyl) amine, m-methylbenzyl chloride, and thiourea to react to prepare a corrosion inhibitor, and while avoiding excessive corrosion of hydrochloric acid, the cleaning agent is made to have an anti-rust effect; magnesium oxide, silicon dioxide, and β-(3,4-epoxycyclohexane) ethyltrimethoxysilane are then used to prepare hydrophobic nano-hydroxy magnesium silicate, and the corrosion inhibitor is cross-linked with aluminum sulfate and coated with hydrophobic nano-hydroxy magnesium silicate, which can be adsorbed to the surface of the metal base by adsorption, and during the cleaning process, the cross-linked structure is hydrolyzed by hydrochloric acid, deionized water, etc., and the hydrophobic nano-hydroxy magnesium silicate is released and deposited at the dent defect of the metal surface. The low-corrosion rust removal foam cleaning agent prepared by the present invention has the effect of rust prevention and repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cleaning agents, in particular to a low-corrosion rust-removing foam cleaning agent and a preparation method thereof. Background Art

[0002] Metal materials are the main materials used to process various mechanical parts and precision components. During use and storage, metal materials will accumulate stains and rust. In order to ensure the quality, service life and performance reliability of metal products, metal materials need to be treated with surface decontamination and rust removal.

[0003] Chemical rust removal is the current development direction of rust removers, with the advantages of good effect, high efficiency, simple process operation and low cost. The existing traditional chemical rust removal usually uses strong acid, which can react chemically with metal oxides to generate soluble salts, thereby achieving the purpose of rust removal. However, during the treatment process, the metal is prone to hydrogen embrittlement and over-corrosion, which affects the strength of the metal itself. After the rust removal is completed, the dents on the metal surface will accelerate the secondary corrosion of the metal, affect the metal's dimensional accuracy and surface quality, and even cause the metal's strength, plasticity, toughness and other mechanical properties to deteriorate, reduce service life, and reduce safety and reliability.

[0004] Therefore, the preparation of a cleaning agent with low corrosion, rust removal and dent defect filling has broad market prospects. Summary of the invention

[0005] The object of the present invention is to provide a low-corrosion rust-removing foam cleaning agent and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A low-corrosion foam cleaning agent for rust removal comprises a component A and a component B; the component A is prepared from a corrosion inhibitor, hydrophobic nano-hydroxy magnesium silicate and aluminum sulfate; the component B is prepared from hydrochloric acid, a surfactant and deionized water.

[0008] Furthermore, the corrosion inhibitor is prepared by reacting an imidazoline intermediate, m-methylbenzyl chloride and thiourea.

[0009] Furthermore, the imidazoline intermediate is prepared by reacting myristic acid and tris(2-aminoethyl)amine.

[0010] Furthermore, the surfactant is prepared by mixing fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyl dimethylamine.

[0011] Furthermore, the hydrophobic nano-hydroxy magnesium silicate is prepared from magnesium oxide, silicon dioxide, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane.

[0012] Furthermore, a method for preparing a low-corrosion rust-removing foam cleaning agent comprises the following preparation steps:

[0013] (1) Deionized water, anhydrous ethanol, nano-hydroxy magnesium silicate, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane are mixed in a mass ratio of 1:1:0.1:0.06 to 1:1:0.2:0.12, reacted at 40 to 90° C. for 110 to 130 minutes, centrifuged at 1500 r / min for 5 to 15 minutes, and the precipitate was taken, washed with deionized water for 2 to 4 times, and dried at 60° C. for 24 hours to obtain hydrophobic nano-hydroxy magnesium silicate;

[0014] (2) mixing the imidazoline intermediate and m-methylbenzyl chloride in a mass ratio of 1:1.0 to 1:1.2, reacting at 100 to 120° C. for 2 to 4 hours, cooling to room temperature, adding thiourea in an amount 2 to 3 times the mass of the imidazoline intermediate, and reacting at 110 to 120° C. for 1 to 2 hours to obtain a corrosion inhibitor;

[0015] (3) Hydrophobic nano-hydroxy magnesium silicate, corrosion inhibitor, aluminum sulfate, hydrazine hydrate, and deionized water were mixed in a mass ratio of

[0016] 3:0.025:0.25:0.25:50~6:0.05:0.50:0.50:50, react at 50~60℃ for 7~9h, and centrifuge at 1500r / min

[0017] 5 to 15 minutes, take the precipitate, wash it with deionized water for 2 to 4 times, and dry it at 60°C for 24 hours to obtain component A; mix 38% hydrochloric acid, a surfactant, and deionized water in a mass ratio of 1.5:1:8 to 2.0:1:10, and stir at 100 to 200 rpm for 10 to 20 minutes to obtain component B; encapsulate component A and component B separately to obtain a low-corrosion rust removal foam cleaning agent.

[0018] Furthermore, the preparation method of the nano-hydroxy magnesium silicate described in step (1) is: magnesium oxide, silicon dioxide, and deionized water are mixed in a mass ratio of 0.09:0.10:1-0.11:0.12:1, sodium hydroxide solution is added until the solution pH is 13-14, and then the reaction is carried out at a pressure of 1.6-9.6 MPa, a temperature of 200-300°C, and a stirring speed of 400-600 rpm for 40-60 hours, and the washing solution is washed with distilled water until the pH value of the washing solution is 6-7, dried at 80°C for 6-8 hours, and ground for 5-10 minutes. Then, the ball milling is carried out for 40-90 minutes at a ball-to-material ratio of 1.2:1-1.5:1, and the drying is carried out at 80°C for 3-5 hours to obtain nano-hydroxy magnesium silicate.

[0019] Furthermore, the preparation method of the imidazoline intermediate described in step (2) is: myristic acid and tri(2-aminoethyl)amine are mixed in a mass ratio of 1:1.0 to 1:1.2, reacted at 8 kPa and 150 to 170 ° C for 3 to 5 hours, then heated to 190 to 210 ° C, reacted at 5 kPa and nitrogen atmosphere for 3 to 5 hours, and cooled to room temperature to prepare the imidazoline intermediate.

[0020] Furthermore, the surfactant in step (3) is prepared by mixing fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyldimethylamine in a mass ratio of 1:0.6 to 1:0.8.

[0021] Furthermore, when using the low-corrosion rust-removing foam cleaning agent prepared by the preparation method of the low-corrosion rust-removing foam cleaning agent, component A and component B are mixed in a mass ratio of 1:30 to 1:50.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The low-corrosion rust-removing foam cleaning agent of the present invention comprises component A consisting of a corrosion inhibitor, hydrophobic nano-hydroxy magnesium silicate, and aluminum sulfate, and component B consisting of hydrochloric acid, a surfactant, and deionized water. The two components are mixed and used during the cleaning process to achieve the effects of rust prevention and repair.

[0024] Firstly, the corrosion inhibitor is prepared from myristic acid, tri(2-aminoethyl)amine, m-methylbenzyl chloride and thiourea; myristic acid and tri(2-aminoethyl)amine are subjected to amidation reaction and cyclization reaction to synthesize an imidazoline intermediate, which can be arranged on the metal surface and extend outward to form a hydrophobic protective layer, so that the cleaning agent has an anti-rust effect; then, the imidazoline quaternary ammonium salt is synthesized by quaternization reaction with m-methylbenzyl chloride, and finally, the corrosion inhibitor is reacted with thiourea to prepare the corrosion inhibitor, which contains multiple polar functional groups and can undergo adsorption reaction with the metal surface charge, so that the protective layer is firmly attached to the surface of the metal substrate, thereby enhancing the anti-rust effect of the cleaning agent.

[0025] Secondly, nano-hydroxy magnesium silicate is prepared by using magnesium oxide and silicon dioxide, and then β-(3,4-epoxycyclohexane)ethyltrimethoxysilane is grafted onto the surface of nano-hydroxy magnesium silicate to prepare hydrophobic nano-hydroxy magnesium silicate, which can be deposited in the dent defects on the metal surface, so that the cleaning agent has a repairing effect; then, the amino group in the corrosion inhibitor reacts with the epoxy group of β-(3,4-epoxycyclohexane)ethyltrimethoxysilane and is grafted onto the surface of the hydrophobic nano-hydroxy magnesium silicate, and then the sulfur in the corrosion inhibitor cross-links with aluminum sulfate to coat the hydrophobic nano-hydroxy magnesium silicate. The coated hydrophobic nano-hydroxy magnesium silicate is adsorbed onto the metal surface through adsorption with the metal surface. In the actual cleaning process, as the A component and the B component are mixed, the cross-linking structure formed by the corrosion inhibitor and the aluminum sulfate is gradually hydrolyzed by the B component, releasing the hydrophobic nano-hydroxy magnesium silicate, which is deposited at the dent defects and adsorbed on the metal surface through intermolecular attraction, playing a repairing role in the metal matrix, so that the cleaning agent achieves a repairing effect. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the low-corrosion rust removal foam cleaning agent prepared in the following examples are as follows:

[0028] The components A and B of the low-corrosion rust-removing foam cleaning agent prepared in the embodiment and the comparative example were mixed at a mass ratio of 1:40, sprayed on the hot-rolled steel plate, and allowed to stand for 45 minutes to obtain a hot-rolled steel plate treated with the low-corrosion rust-removing foam cleaning agent;

[0029] Anti-rust effect: The rust area of ​​the hot-rolled steel plate treated with low-corrosion rust removal foam cleaning agent is tested according to JIS Z2371 and judged on 10 levels. The larger the number, the smaller the corrosion rate and the better the anti-rust effect.

[0030] Repair effect: The rust depth of the hot-rolled steel plate treated with low-corrosion rust removal foam cleaning agent was tested according to GB / T14977.

[0031] Example 1

[0032] (1) Magnesium oxide, silicon dioxide and deionized water were mixed in a mass ratio of 0.09:0.10:1, sodium hydroxide solution was added until the solution pH was 13, and then the mixture was reacted for 40 hours at a pressure of 1.6 MPa, a temperature of 200° C. and a stirring speed of 400 rpm, and then the mixture was washed with distilled water until the washing solution pH was 6, dried at 80° C. for 6 hours, ground for 5 minutes, ball-milled for 40 minutes at a ball-to-material ratio of 1.2:1, and dried at 80° C. for 3 hours to obtain nano-hydroxy magnesium silicate;

[0033] (2) Deionized water, anhydrous ethanol, nano-hydroxy magnesium silicate, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane were mixed in a mass ratio of 1:1:0.1:0.06, reacted at 40° C. for 110 min, centrifuged at 1500 r / min for 5 min, the precipitate was taken, washed twice with deionized water, and dried at 60° C. for 24 h to obtain hydrophobic nano-hydroxy magnesium silicate;

[0034] (3) Myristic acid and tri(2-aminoethyl)amine were mixed in a mass ratio of 1:1, reacted at 8 kPa and 150° C. for 3 h, then heated to 190° C., reacted at 5 kPa and nitrogen atmosphere for 3 h, and cooled to room temperature to prepare an imidazoline intermediate; the imidazoline intermediate and m-methylbenzyl chloride were mixed in a mass ratio of 1:1, reacted at 100° C. for 2 h, cooled to room temperature, thiourea twice the mass of the imidazoline intermediate was added, and reacted at 110° C. for 1 h to obtain a corrosion inhibitor;

[0035] (4) Fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyldimethylamine are mixed in a mass ratio of 1:0.6 to prepare a surfactant; hydrophobic nano-hydroxy magnesium silicate, corrosion inhibitor, aluminum sulfate, hydrazine hydrate, and deionized water are mixed in a mass ratio of 3:0.025:0.25:0.25:50, reacted at 50°C for 7 hours, centrifuged at 1500 r / min for 5 minutes, the precipitate is taken, washed twice with deionized water, and dried at 60°C for 24 hours to obtain component A; hydrochloric acid with a mass fraction of 38%, a surfactant, and deionized water are mixed in a mass ratio of 1.5:1:8, stirred at 100 rpm for 10 minutes to obtain component B; component A and component B are encapsulated separately to obtain a low-corrosion rust removal foam cleaning agent.

[0036] Example 2

[0037] (1) Magnesium oxide, silicon dioxide and deionized water were mixed in a mass ratio of 0.10:0.11:1, sodium hydroxide solution was added until the solution pH was 13.5, and then reacted for 50 hours at a pressure of 5.6 MPa, a temperature of 250° C. and a stirring speed of 500 rpm, washed with distilled water until the washing solution pH was 6.5, dried at 80° C. for 7 hours, ground for 8 minutes, ball milled for 75 minutes at a ball-to-material ratio of 1.35:1, and dried at 80° C. for 4 hours to obtain nano-hydroxy magnesium silicate;

[0038] (2) Deionized water, anhydrous ethanol, nano-hydroxy magnesium silicate, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane were mixed in a mass ratio of 1:1:0.15:0.09, reacted at 75°C for 120 minutes, centrifuged at 1500 r / min for 10 minutes, and the precipitate was taken, washed with deionized water three times, and dried at 60°C for 24 hours to obtain hydrophobic nano-hydroxy magnesium silicate;

[0039] (3) Myristic acid and tri(2-aminoethyl)amine were mixed in a mass ratio of 1:1.1, reacted at 8 kPa and 160° C. for 4 h, then heated to 200° C., reacted at 5 kPa and nitrogen atmosphere for 4 h, and cooled to room temperature to prepare an imidazoline intermediate; the imidazoline intermediate and m-methylbenzyl chloride were mixed in a mass ratio of 1:15, reacted at 110° C. for 3 h, cooled to room temperature, thiourea 2.5 times the mass of the imidazoline intermediate was added, and reacted at 115° C. for 1.5 h to obtain a corrosion inhibitor;

[0040] (4) Fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyldimethylamine are mixed in a mass ratio of 1:0.7 to prepare a surfactant; hydrophobic nano-hydroxy magnesium silicate, corrosion inhibitor, aluminum sulfate, hydrazine hydrate, and deionized water are mixed in a mass ratio of 4.5:0.035:0.35:0.35:50, reacted at 55°C for 8 hours, centrifuged at 1500 r / min for 10 minutes, the precipitate is taken, washed with deionized water for 3 times, and dried at 60°C for 24 hours to obtain component A; hydrochloric acid with a mass fraction of 38%, a surfactant, and deionized water are mixed in a mass ratio of 1.75:1:9, stirred at 150 rpm for 15 minutes to obtain component B; component A and component B are encapsulated separately to obtain a low-corrosion rust removal foam cleaning agent.

[0041] Example 3

[0042] (1) Magnesium oxide, silicon dioxide and deionized water were mixed in a mass ratio of 0.11:0.12:1, sodium hydroxide solution was added until the solution pH was 14, and then the mixture was reacted for 60 hours at a pressure of 9.6 MPa, a temperature of 300° C. and a stirring speed of 600 rpm, washed with distilled water until the washing solution pH was 7, dried at 80° C. for 8 hours, ground for 10 minutes, ball-milled for 90 minutes at a ball-to-material ratio of 1.5:1, and dried at 80° C. for 5 hours to obtain nano-hydroxy magnesium silicate;

[0043] (2) Deionized water, anhydrous ethanol, nano-hydroxy magnesium silicate, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane were mixed in a mass ratio of 1:1:0.2:0.12, reacted at 90° C. for 130 min, centrifuged at 1500 r / min for 15 min, the precipitate was taken, washed with deionized water 4 times, and dried at 60° C. for 24 h to obtain hydrophobic nano-hydroxy magnesium silicate;

[0044] (3) Myristic acid and tri(2-aminoethyl)amine were mixed in a mass ratio of 1:1.2, reacted at 8 kPa and 170° C. for 5 h, then heated to 210° C., reacted at 5 kPa and nitrogen atmosphere for 5 h, and cooled to room temperature to prepare an imidazoline intermediate; the imidazoline intermediate and m-methylbenzyl chloride were mixed in a mass ratio of 1:1.2, reacted at 120° C. for 4 h, cooled to room temperature, thiourea 3 times the mass of the imidazoline intermediate was added, and reacted at 120° C. for 2 h to obtain a corrosion inhibitor;

[0045] (4) Fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyldimethylamine are mixed in a mass ratio of 1:0.8 to prepare a surfactant; hydrophobic nano-hydroxy magnesium silicate, corrosion inhibitor, aluminum sulfate, hydrazine hydrate, and deionized water are mixed in a mass ratio of 6:0.05:0.5:0.5:50, reacted at 60°C for 9 hours, centrifuged at 1500 r / min for 15 minutes, the precipitate is taken, washed with deionized water for 4 times, and dried at 60°C for 24 hours to obtain component A; hydrochloric acid with a mass fraction of 38%, a surfactant, and deionized water are mixed in a mass ratio of 2:1:10, stirred at 200 rpm for 20 minutes to obtain component B; component A and component B are encapsulated separately to obtain a low-corrosion rust removal foam cleaning agent.

[0046] Comparative Example 1

[0047] The difference between Comparative Example 1 and Example 2 is that there is no step (2), and step (4) is changed to: fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyl dimethylamine are mixed in a mass ratio of 1:0.7 to prepare a surfactant, nano-hydroxy magnesium silicate, corrosion inhibitor, aluminum sulfate, hydrazine hydrate, and deionized water are mixed in a mass ratio of 4.5:0.035:0.35:0.35:50, reacted at 55°C for 8 hours, centrifuged at 1500r / min for 10 minutes, and the precipitate liquid is taken, washed with deionized water for 3 times, and dried at 60°C for 24 hours to obtain component A; hydrochloric acid with a mass fraction of 38%, a surfactant, and deionized water are mixed in a mass ratio of 1.75:1:9, stirred at 150rpm for 15 minutes to obtain component B; component A and component B are encapsulated separately to obtain a low-corrosion rust removal foam cleaning agent. The remaining steps are the same as those in Example 2.

[0048] Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 2 is that step (3) is different, and step (3) is changed to: tris (2-aminoethyl) amine is mixed in a mass ratio of 1:1.1, reacted at 8kPa and 160°C for 4h, then heated to 200°C, reacted at 5kPa and nitrogen atmosphere for 4h, and cooled to room temperature to prepare an imidazoline intermediate; the imidazoline intermediate and m-methylbenzyl chloride are mixed in a mass ratio of 1:15, reacted at 110°C for 3h, cooled to room temperature, thiourea 2.5 times the mass of the imidazoline intermediate is added, and reacted at 115°C for 1.5h to obtain a corrosion inhibitor. The remaining steps are the same as in Example 2.

[0050] Comparative Example 3

[0051] The difference between Comparative Example 3 and Example 2 is that there are no steps (1) and (2), and step (4) is changed to: fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyl dimethylamine are mixed in a mass ratio of 1:0.7 to prepare a surfactant, aluminum sulfate, hydrazine hydrate, and deionized water are mixed in a mass ratio of 4.5:0.035:0.35:0.35:50, reacted at 55°C for 8 hours, centrifuged at 1500r / min for 10 minutes, the precipitate liquid is taken, washed with deionized water for 3 times, and dried at 60°C for 24 hours to obtain component A; hydrochloric acid with a mass fraction of 38%, a surfactant, and deionized water are mixed in a mass ratio of 1.75:1:9, stirred at 150rpm for 15 minutes to obtain component B; component A and component B are encapsulated separately to obtain a low-corrosion rust removal foam cleaning agent. The remaining steps are the same as those of Example 2.

[0052] Comparative Example 4

[0053] The difference between Comparative Example 4 and Example 2 is that step (3) is different, and step (3) is changed to: myristic acid and tris (2-aminoethyl) amine are mixed in a mass ratio of 1:1.1, reacted at 8 kPa and 160 ° C for 4 hours, then heated to 200 ° C, reacted at 5 kPa and nitrogen atmosphere for 4 hours, and cooled to room temperature to prepare an imidazoline intermediate; the imidazoline intermediate and m-methylbenzyl chloride are mixed in a mass ratio of 1:15, reacted at 110 ° C for 3 hours, and a corrosion inhibitor is obtained. The remaining steps are the same as in Example 2.

[0054] Comparative Example 5

[0055] The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: sodium sulfate of fatty alcohol polyoxyethylene ether and N-dodecyl dimethylamine are mixed in a mass ratio of 1:0.7 to obtain a surfactant; hydrophobic nano-hydroxy magnesium silicate, corrosion inhibitor, hydrazine hydrate and deionized water are mixed in a mass ratio of 4.5:0.035:0.35:50, reacted at 55°C for 8 hours, centrifuged at 1500r / min for 10 minutes, and the precipitate is taken, washed with deionized water 3 times, and dried at 60°C for 24 hours to obtain component A; hydrochloric acid with a mass fraction of 38%, a surfactant and deionized water are mixed in a mass ratio of 1.75:1:9, stirred at 150rpm for 15 minutes to obtain component B; component A and component B are encapsulated separately to obtain a low-corrosion rust removal foam cleaning agent. The remaining steps are the same as those in Example 2.

[0056] Effect example

[0057] Table 1 below shows the performance analysis results of the low-corrosion rust removal foam cleaning agents of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0058] Table 1

[0059]

[0060] From the comparison of the salt spray test grade data of the embodiment and the comparative example in Table 1, it can be found that the reaction of myristic acid and tris (2-aminoethyl) amine can form a hydrophobic film on the metal surface to prevent the metal from rusting again, so that the cleaning agent has an anti-rust effect, and then further reacts with m-methylbenzyl chloride and thiourea to enhance the adsorption force between the metal matrix and the homemade sustained-release agent, which helps to improve the anti-rust effect. In addition, after the grafting of β-(3,4-epoxycyclohexane) ethyltrimethoxysilane, nano-hydroxy magnesium silicate can be deposited on the metal surface to form a hydrophobic layer, which increases the anti-rust effect; from the comparison of the corrosion depth data of the embodiment and the comparative example in Table 1, it can be found that the reaction of myristic acid, tris (2-aminoethyl) The corrosion inhibitor prepared from amine, m-methylbenzyl chloride and thiourea can separate hydrochloric acid from the metal matrix, and can avoid the corrosion of the metal matrix by hydrochloric acid during the rust removal process. After the addition of hydrophobic nano-hydroxy magnesium silicate, it is adsorbed on the metal surface through intermolecular attraction, and plays a repairing role in the metal matrix. The bridging effect of β-(3,4-epoxycyclohexane)ethyltrimethoxysilane allows the corrosion inhibitor to cross-link with aluminum sulfate to coat the hydrophobic nano-hydroxy magnesium silicate, which protects the hydrophobic nano-hydroxy magnesium silicate and drives the hydrophobic nano-hydroxy magnesium silicate to be deposited on the metal surface. As the cross-linking structure is continuously hydrolyzed, the hydrophobic nano-hydroxy magnesium silicate is released, thereby enhancing the repair effect.

[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A low-corrosion rust-removing foam cleaning agent, characterized in that: The low-corrosion rust removal foam cleaning agent is prepared by the following steps: (1) deionized water, anhydrous ethanol, nano-hydroxy magnesium silicate, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane are mixed in a mass ratio of 1:1:0.1:0.06 to 1:1:0.2:0.12, reacted at 40 to 90° C. for 110 to 130 minutes, centrifuged at 1500 r / min for 5 to 15 minutes, and the precipitate was taken, washed with deionized water for 2 to 4 times, and dried at 60° C. for 24 hours to obtain hydrophobic nano-hydroxy magnesium silicate; (2) mixing the imidazoline intermediate and m-methylbenzyl chloride in a mass ratio of 1:1.0 to 1:1.2, reacting at 100 to 120° C. for 2 to 4 hours, cooling to room temperature, adding thiourea in an amount 2 to 3 times the mass of the imidazoline intermediate, and reacting at 110 to 120° C. for 1 to 2 hours to obtain a corrosion inhibitor; (3) Mixing hydrophobic nano-hydroxy magnesium silicate, corrosion inhibitor, aluminum sulfate, hydrazine hydrate, and deionized water in a mass ratio of 3:0.025:0.25:0.25:50-6:0.05:0.50:0.50:50, reacting at 50-60°C for 7-9 hours, centrifuging at 1500r / min for 5-15 minutes, taking the precipitate liquid, washing it with deionized water for 2-4 times, and drying it at 60°C for 24 hours to obtain component A; mixing hydrochloric acid with a mass fraction of 38%, a surfactant, and deionized water in a mass ratio of 1.5:1:8-2.0:1:10, stirring at 100-200rpm for 10-20 minutes to obtain component B; mixing component A and component B in a mass ratio of 1:30-1:50 to obtain a low-corrosion rust removal foam cleaning agent; The preparation method of the nano-hydroxy magnesium silicate described in step (1) is as follows: magnesium oxide, silicon dioxide and deionized water are mixed in a mass ratio of 0.09:0.10:1-0.11:0.12:1, sodium hydroxide solution is added until the solution pH is 13-14, and then the mixture is reacted for 40-60 hours at a pressure of 1.6-9.6 MPa, a temperature of 200-300° C. and a stirring speed of 400-600 rpm, and the mixture is washed with distilled water until the washing solution pH is 6-7, dried at 80° C. for 6-8 hours, ground for 5-10 minutes, ball-milled for 40-90 minutes at a ball-to-material ratio of 1.2:1-1.5:1, and dried at 80° C. for 3-5 hours to obtain nano-hydroxy magnesium silicate; The preparation method of the imidazoline intermediate described in step (2) is: myristic acid and tris (2-aminoethyl) amine are mixed in a mass ratio of 1:1.0 to 1:1.2, reacted at 8kPa and 150 to 170°C for 3 to 5h, then heated to 190 to 210°C, reacted at 5kPa and nitrogen atmosphere for 3 to 5h, and cooled to room temperature to prepare the imidazoline intermediate.

2. A low-corrosion rust-removing foam cleaning agent according to claim 1, characterized in that: The surfactant is prepared by mixing fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyl dimethylamine.

3. A low-corrosion rust-removing foam cleaning agent according to claim 2, characterized in that: The surfactant in step (3) is prepared by mixing fatty alcohol polyoxyethylene ether sodium sulfate and N-dodecyl dimethylamine in a mass ratio of 1:0.6 to 1:0.8.

Citation Information

Patent Citations

  • Thioureido modified imidazoline derivative corrosion inhibitor and preparation method and application of thioureido modified imidazoline derivative corrosion inhibitor

    CN108467366A

  • Cleaning agent, as well as preparation method and use thereof

    CN109234047A